2016
DOI: 10.1016/j.str.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Ring Separation Highlights the Protein-Folding Mechanism Used by the Phage EL-Encoded Chaperonin

Abstract: Summary Chaperonins are ubiquitous, ATP dependent protein-folding molecular machines that are essential for all forms of life. Bacteriophage φEL encodes its own chaperonin to presumably fold exceedingly large viral proteins via profoundly different nucleotide-binding conformations. Our structural investigations indicate that ATP likely binds to both rings simultaneously and that a misfolded substrate acts as the trigger for ATP hydrolysis. More importantly, the φEL complex dissociates into two single rings res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 41 publications
1
37
6
Order By: Relevance
“…In this case, the apo form of the chaperonin is tetradecameric. However, upon nucleotide binding, the oligomer dissociates into two heptameric rings with a largely expanded cavity, able to accommodate larger substrate proteins than other known chaperonins (Molugu et al, 2016). Thus, similar to what was proposed for the mitochondrial and T. thermophilus chaperonins, phi-EL seems to incorporate a single-ringed intermediate in its reaction cycle.…”
Section: Divergent Mechanisms? Insight From Structural Studies Of Thementioning
confidence: 99%
“…In this case, the apo form of the chaperonin is tetradecameric. However, upon nucleotide binding, the oligomer dissociates into two heptameric rings with a largely expanded cavity, able to accommodate larger substrate proteins than other known chaperonins (Molugu et al, 2016). Thus, similar to what was proposed for the mitochondrial and T. thermophilus chaperonins, phi-EL seems to incorporate a single-ringed intermediate in its reaction cycle.…”
Section: Divergent Mechanisms? Insight From Structural Studies Of Thementioning
confidence: 99%
“…The dilution buffer with ADP also contained 0.08 % n-octyl-β-D-glucopyranoside. 10 Subsequently the mixture was incubated at room temperature for 5 min. Holey carbon supported copper-grids (Quantifoil R2/1 300 mesh) were plasma-cleaned for 30 s (Harrick Plasma) immediately before use.…”
Section: Cryo-electron Microscopy and Single Particle Analysismentioning
confidence: 99%
“…Two crystal forms were identified that diffracted to 4.03 and 3.54 Å resolution ( Table 1). The structure was solved by molecular replacement at 6.8 Å resolution using the cryo-EM map of the ɸEL-ATP tetradecamer as a search model (EMD-6492) [10]. The seven-fold non-crystallographic symmetry was then employed to extend the phases to 3.54 Å, resulting in an electron density map of sufficient quality to build an atomic model.…”
Section: Crystal Structures Of ɸEl In Presence Of Atp•befxmentioning
confidence: 99%
See 2 more Smart Citations